EFFECTS OF ZIZIPHUS JUJUBA HONEY ON HYPERGLYCEMIA AND COGNITIVE IMPAIRMENTS INDUCED BY STREPTOZOTOCIN (The Research of Medical Science Review, 2024)
This study explores the therapeutic potential of Ziziphus jujuba honey in alleviating hyperglycemia and cognitive impairments induced by streptozotocin in adult mice. Streptozotocin is known to induce diabetes and associated neurological deficits, making it a suitable model for investigating the protective effects of natural remedies. The research involved administering varying doses of Ziziphus jujuba honey to diabetic mice over a specified period. Assessments of blood glucose levels and cognitive function, evaluated through behavioral tests, revealed that honey treatment significantly reduced hyperglycemia and improved cognitive performance compared to control groups. These findings suggest that Ziziphus jujuba honey may offer a complementary approach to managing diabetes and its cognitive complications, warranting further investigation into its mechanisms of action and potential clinical applications.